Riwayat-Riwayat Perawi Berdusta Dan Dituduh Berdusta Dalam Periwayatan Hadith - Osman, M. N. A.; Ramle, M. R.; Zali, M. A.; Ismail, M. Z. (Universiti Sains Islam Malaysia, 2024)
When a narrator is judged by a critic with a liar or lying accused, then the allegations will bring down the dignity of narrated narrations of the hadiths. This ia because of their indirect belief that the narrator is disputed. Hence, the hadith scholars place the trust of narrators as one of the important elements that must be fulfilled before a hadith is received. It is one of the branches in the weak division of the hadith. Then the practice of such hadiths should be avoided. This study aims to look at the definition of lies and accused of lying, as well as see also the history of appearing lies in the history. Besides, ia is also seen from the angle of al-jarah wa al-ta`dil in accepting the brand registration. Hence, this study will see some views from the side of al-jarah wa al-ta`dil to conclude the decision whether their narrative is accepted or otherwise. This study uses a qualitative study in the form of document analysis. The results of this study found that the hadiths scholars differed in views to accept the reconciliayion of the brand's recitals which had been repented from the reprimand of some who received and others who did not receive their narrative. This knowledge has its own singnificance so that the researchers can evaluate each event before accepting it as a practice. Furthermore, this study also explains to us some methodology regarding al-jarah wa al-ta`dil knowledge when assessing a narrator.